As the dust settles...n; Never too young to learn; A tribute to Mang Cesar [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1994)
Summary: Deals with the re-evaluation of movie industry after the Manila Filmfest scandal; the alleged distribution of "pornographic cartoons" for sex education classes in the elementary and high school levels and the national artist, Cesar Legaspi.
Contents: As the dust settles...n (15 min.) -- Never too young to learn (15 min.) -- A tribute to Mang Cesar (15 min.)
VHS.
Keywords: Legaspi, Cesar; Motion picture industry -- Philippines; Caricatures and cartoons -- Social aspects -- Philippines